Contractual Justice in Traditional Market Leasing: An Ijārah-Based Analysis at Pasar Kalangan - Okta priansa, Rizki; Kurniawan; Fatimah, Siti; kadarsih, Sri; Dewi , Hasna (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study analyzes the practice of kiosk rental (ijārah) in Kalangan Market, Mendahara Subdistrict, Tanjung Jabung Timur Regency, from the perspectives of Islamic law and positive legal regulations. Field observations show that rental transactions are conducted verbally without written contracts, with monthly cash payments of IDR 30,000. Most traders (approximately 70%) fail to pay on time, and the absence of strict sanctions indicates a weak commitment to the agreed contract. In Islamic law, a valid ijārah contract requires clarity regarding the rental object, the benefit obtained, the agreed compensation (ujrah), and a valid offer and acceptance (ijab and qabul). The current practice poses risks of injustice and imbalances in the rights and obligations between tenants and market managers. Therefore, reforming the rental system based on the principles of justice, clarity, and accountability, as mandated in Islamic commercial jurisprudence (muʿāmalah) and positive law, is essential for establishing a professional, transparent, and sustainable market governance framework.